The The Mediating Role of Employee Engagement in the Relationship between Transformational and Transactional Leadership and Organizational Commitment - Karmilaturrahman; Pardiman; Ahmad Subhan Mahardani (LP2M IAIN Palopo, 2026)
This study aims to examine the effects of transformational and transactional leadership on organizational commitment, with employee engagement as a mediating variable at PT Charoen Pokphand Indonesia Tbk, Bima, West Nusa Tenggara. A quantitative approach was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 99 employees and analyzed using SmartPLS software. The results indicate that transformational leadership has a positive and significant effect on organizational commitment and employee engagement, while transactional leadership has a positive and significant effect on employee engagement but does not significantly affect organizational commitment. Furthermore, employee engagement has a positive and significant effect on organizational commitment but does not significantly mediate the relationship between transformational and transactional leadership and organizational commitment. These findings suggest that organizational commitment is more strongly influenced by the direct effects of leadership, particularly transformational leadership, rather than through the mediating role of employee engagement. This study contributes to the organizational behavior literature and provides practical implications for organizations in determining effective leadership styles to enhance employee commitment.